The use of Tricuspid Annular Plane Systolic Excursion and Tissue Doppler Imaging Velocities for the Estimation of Pulmonary Hypertension and Right Ventricular Function in Mechanically Ventilated Patients - Papaioannou, Vasilios; Pneumatikos, Ioannis (IntechOpen, 2011)
None